2009
DOI: 10.2320/matertrans.mer2008179
|View full text |Cite
|
Sign up to set email alerts
|

Formation, Thermal Stability and Mechanical Properties of Bulk Glassy Alloys with a Diameter of 20 mm in Zr-(Ti,Nb)-Al-Ni-Cu System

Abstract: Bulk glassy alloy rods with a diameter of 20 mm were produced for Zr 61 Ti 2 Nb 2 Al 7:5 Ni 10 Cu 17:5 and Zr 60 Ti 2 Nb 2 Al 7:5 Ni 10 Cu 18:5 by a tilt casting method. The replacement of Zr by a small amount of Ti and Nb caused a distinct increase in the maximum diameter from 16 mm for Zr 65 Al 7:5 Ni 10 Cu 17:5 to 20 mm, accompanying the decrease in liquidus temperature and the increase in reduced glass transition temperature. The primary precipitation phase from supercooled liquid also shows a distinct cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In the present work, the deformation evolution and mechanisms of a Zr-based BMG under three-point bending tests are investigated. A Zr 65 Cu 17.5 Ni 10 Al 7.5 BMG is selected for its good glass forming ability, and has also been studied extensively due to its potential engineering applications [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…In the present work, the deformation evolution and mechanisms of a Zr-based BMG under three-point bending tests are investigated. A Zr 65 Cu 17.5 Ni 10 Al 7.5 BMG is selected for its good glass forming ability, and has also been studied extensively due to its potential engineering applications [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the eutectic Zr 55 Al 10 Cu 30 Ni 5 alloy rods retained a glassy phase in the diameter range up to 30 mm 7,8 in the case of copper mold suction casting and 32 mm using copper mold cap casting 44 . Similarly, the maximum diameter for the hypoeutectic‐type glassy alloys has been reported to be at least 20 mm for Zr 60 Al 10 Ni 10 Cu 20 , Zr 61 Ti 2 Nb 2 Al 7.5 Ni 10 Cu 17.5 , Zr 60 Ti 2 Nb 2 Al 7.5 Ni 10 Cu 18.5 , and Zr 65 Al 7.5 Ni 10 Cu 15.5 Pd 2 (K. S. Son, X. M. Wang, A. Inoue, personal communication) 57 and 16 mm for Zr 65 Al 7.5 Ni 10 Cu 17.5 58 by copper mold tilt casting. We have also confirmed that the thermal stability parameters of T g , T x , and Δ T x (= T x − T g ), static mechanical properties of Young's modulus, yield strength and plastic strain, and deformation and fracture behaviors via shear sliding along the maximum shear stress plane and then catastrophic final rupture are independent of the picking position and the picking angle to the longitudinal direction of the cast alloy rod as well as the rod dimension in the diameter range up to 20 mm 59 .…”
Section: Glass‐forming Ability Of Zr‐based Hypoeutectic Glassy Alloysmentioning
confidence: 99%